Quality of Working Life of Personnel under the Subdistrict Administrative Organization Taphanhin District Area Phichit Province - Sanitrak, Rachanon; Bodeerat , Chot; Phongrod, Yuvadee (Academic MCU Buriram Journal, 2025)
This research aims to study the level of quality of work life. To compare the opinions of personnel under the Subdistrict Administrative Organization regarding their quality of work life, classified according to personal factors. And to study strategies for promoting and developing the quality of work life for personnel under the Subdistrict Administrative Organization in the Taphanhin District, Phichit Province. The research employs a mixed-methods approach, combining both quantitative and qualitative research methods. The quantitative aspect of the research focuses on the population of 105 subdistrict administrative officers (SAO personnel) from 10 Subdistrict Administrative Organizations in the Taphanhin District, Phichit Province. Data is collected using a questionnaire with a reliability coefficient of 0.96. The statistical methods used in the research include percentages, means, standard deviations, as well as T-test and F-test for hypothesis testing. The qualitative aspect of the research involves interviews with key informants, specifically 10 SAO chiefs from the 10 Subdistrict Administrative Organizations in the Taphanhin District, Phichit Province. The interviews aim to gather their opinions on strategies for promoting and developing the quality of work life for personnel under the Subdistrict Administrative Organization in the Taphanhin District, Phichit Province. The research results found that: 1. The quality of work-life of personnel in the sub-district administrative organizations in the Taphanhin District, Phichit Province, across all 8 areas, is generally at a high level. The area with the highest average score is collaboration and relationships with others. 2. Personal factors related to marital status and work experience significantly affect work-life quality, with statistical significance at .05. However other factors do not show a significant difference in their effect on work-life quality. 3. The approaches to promoting and developing work-life quality for personnel in the sub-district administrative organizations in the Taphanhin District, Phichit Province, based on interviews with the mayors of these organizations, suggest that current compensation is insufficient or does not align with the current cost of living. If the regulations are amended to better match the economic conditions, it would positively impact work life quality.